2016
DOI: 10.1515/znc-2015-0265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel pyrimidines derived from 6-aryl-5-cyano-2-thiouracil

Abstract: Starting from 6-aryl-5-cyano-2-thiouracil derivative 1a-f, a series of novel thiazolo[3,2-a]pyrimidines 4a-f were synthesized. The mechanism and the regioselectivity of the studied reactions are discussed. In addition, a series of tetrahydro-4-H-pyrimido[2,1-b][1,3]thiazines 7a-e and 2-((ethoxymethyl)thio)-4-aryl-1,6-dihydropyrimidines 9b,c,e were synthesized. The anti-microbial activities of some of the prepared compounds were screened, and the results revealed that compounds 3c and 4c were more active than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The simplicity and versatility of this process led to the production of a wide range of bioactive agents. Based on these findings and in combination with our interest in anticancer agents [28–31] along with our previous research on pyrimidine‐containing molecules, [32–34] we report, herein, a series of new hydrazone derivatives 4 a – l (Scheme 1) containing spirocyclic aminopyrimidine and aryl alkanesulfonate moieties. To access the starting compound, we used a Biginelli reaction which is an example of the multicomponent reaction [35] by which cyclohexanone, malononitrile and thiourea were reacted in one‐pot process to produce the spirocyclic pyrimidine.…”
Section: Introductionmentioning
confidence: 72%
“…The simplicity and versatility of this process led to the production of a wide range of bioactive agents. Based on these findings and in combination with our interest in anticancer agents [28–31] along with our previous research on pyrimidine‐containing molecules, [32–34] we report, herein, a series of new hydrazone derivatives 4 a – l (Scheme 1) containing spirocyclic aminopyrimidine and aryl alkanesulfonate moieties. To access the starting compound, we used a Biginelli reaction which is an example of the multicomponent reaction [35] by which cyclohexanone, malononitrile and thiourea were reacted in one‐pot process to produce the spirocyclic pyrimidine.…”
Section: Introductionmentioning
confidence: 72%
“…There are no licensed antivirals to target viruses of the Coronaviridae family. Based on our experience in the synthesis of bioactive compounds, [4–7] we intended to develop new chemical designs that could be investigated as antiviral agents. Our last studies demonstrated the good bioactivity of spirocyclic thiopyrimidine derivatives as antibacterial agents [8] and this encouraged us to explore different series of these compounds to study their antiviral activity.…”
Section: Introductionmentioning
confidence: 99%